Gaya Mengajar Guru Dalam Proses Belajar Mengajar - Djuwarijah - (Islamic University of Indonesia, 2002)
Teacher with several competencies is important to develop cognitive affective and psychomotor domain. There are several differents of characteristic and study style in learning, so teacher should be adapt the teaching in accordance with students need. There are three teaching styles, authoritarian, laissez faire and democratic style. The democratic style is a good ones to develop all the competence that students have.Key Word: teacher style, teaching-learning process